The Art of Nandung in Indragiri Hulu Regency, Riau: the Study of Performance Form and Value - Suardi, Rofiandri; Utomo, Udi (Catharsis, 2018)
Nandung is an spoken literature used as a lullaby, delivered with poems and chanted by humming. Nandung contains poems about religion, advice, character, and education.At present, Nandung grows as a kind of performing art. This research aims at analyzing the form of Nandung as a performing art and its values. The method used was qualitative. The location of the research was Rengat, Indragiri Hulu Regency, Riau Province. The technique of data retrieval were observation, interview, and document study. The technique of data validity used triangulation source. The technique of data analysis used descriptive analysis. The results of the research are that the form of Nandung performance begins from the preparation, then goes to the main performance. There are 7 (seven) elements in the form of Nandung spoken literature performance, they are, speaker, music accompaniment, stage, costume, audience, poem, and the language used. The values in the poems are, religious value, character value, and education value. This research can broaden the perspective of the readers about Nandung spoken literature and give information about description and knowledge about Nandung spoken literature which is seen from the aspects of the performance and the values in it.